Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

tootles97

  • 3 years ago

solve the system of equations by substitution... f-3g=9 5f+g=-3

  • This Question is Closed
  1. DarthTony
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    do you mean f-3g=9 ?

  2. tootles97
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    yeah

  3. Sujay
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Well, \[g=-5f-3\], according to your information. So I substitute that into \[f-3g=9\]. That means \[f-3(-5f-3)=9\] or \[f+15f+9=9\]. That means \[15f=0\]. So \[f=0\]. Now I substitute 0 in for f: \[g=-5(0)-3\]. So \[g=3\] and \[f=0\] :).

  4. Sujay
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    g=-3*

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy